The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1055/s-0031-1279712
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glycemic Status and Physical Fitness on Oxidative Stress and the Peroxiredoxin System in the Erythrocytes of Non-Insulin-Dependent Type 2 Diabetic Men

Abstract: Poor glycemic control may increase oxidative stress in the erythrocytes of type 2 diabetic men. Good physical fitness seems to be associated with increased peroxiredoxin contents. Therefore, it can be speculated that physical training can contribute to the improvement of the erythrocyte peroxiredoxin system to counteract free radicals in type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Previous studies in patients with T2DM revealed a decrease in antioxidant defense mechanisms and an increase in markers of oxidative damage, especially in patients with diabetes-related complications ( 9 ). Similar results to ours were reported for PRDX1 activity in erythrocytes, which was greater in T2DM patients than in non-diabetic subjects ( 12 ). Another study revealed a high total antioxidant capacity and higher concentrations of lipid peroxidation markers in T2DM patients than in non-diabetic subjects ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in patients with T2DM revealed a decrease in antioxidant defense mechanisms and an increase in markers of oxidative damage, especially in patients with diabetes-related complications ( 9 ). Similar results to ours were reported for PRDX1 activity in erythrocytes, which was greater in T2DM patients than in non-diabetic subjects ( 12 ). Another study revealed a high total antioxidant capacity and higher concentrations of lipid peroxidation markers in T2DM patients than in non-diabetic subjects ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several epidemiological studies with relatively small sample sizes have evaluated the associations of urinary 8-iso-PGF2a and 8-OHdG with blood glucose. A cross-sectional study conducted on 76 Indian Mauritians showed a positive relationship between 8-iso-PGF2a and FPG (31), and similar results were also found by Brinkmann et al (32) and Altomare et al (33). Also, Rytter et al (34) investigated 56 Swedish patients with diabetes and found that urinary 8-iso-PGF2a, but not 8-OHdG, was positively associated with blood glucose.…”
Section: Discussionsupporting
confidence: 79%
“…One of the mechanisms suspected to be at the origin of the RBC deformability improvement in healthy individuals is the greater RBC-NOS activation and RBC NO production noted in response to exercise 16 . In addition, long term training is associated to a reduction in free radical production and improved antioxidant capacity in healthy people and subjects with metabolic diseases 25,26 . In SCA, the metabolic changes that occur during acute exercise, including increased free radical production, can promote HbS polymerization and RBC sickling.…”
Section: Introductionmentioning
confidence: 99%